Parametric study to determine the effect of temperature on oil solidifier performance and the development of a new empirical correlation for predicting effectiveness. Issue 1 (15th June 2015) - Sundaravadivelu, Devi; Suidan, Makram T.; Venosa, Albert D.
Highlights: Removal efficiency of oil solidifier declined with decreasing temperature. Oil removal by solidifiers was highly dependent on oil viscosity. Bulk density of solidifier products had a large impact on removal efficiency. Abstract: Temperature can play a significant role in the efficacy of solidifiers in removing oil slicks on water. We studied and quantified the effect of temperature on the performance of several solidifiers using 5 different types of oils under a newly developed testing protocol by conducting experiments in constant temperature rooms set at 22 °C and 5 °C. The results indicated that solidifier efficiency decreased substantially at the lower temperature, especially at lower application rates. The removal efficiency of the solidifier was in general directly proportional to temperature, except for the heavier oils, where removal by attachment was observed. Solidifier products with lower powder bulk density exhibited the best removal effectiveness. Analysis of experimental data yielded empirical correlations involving certain operational variables such as application rate, temperature, solidifier property (bulk density), and oil property (viscosity). Regression analysis was used to fit a mathematical model to the experimental solidifier effectiveness data.